1980
DOI: 10.1002/pol.1980.180180616
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromism in polydiacetylene solutions

Abstract: A novel planar ↔ nonplanar visual thermochromic conformational transition of polydiacetylene molecules in poor solvents is reported. The conformational transition is associated with both a color change (blue or red ↔ yellow) and a change in the state; the yellow solution (liquid) transforms to a blue or red gel (solid). The color transition occurs within a narrow range of temperature and has a large associated hysteresis. The enthalpy of the conformational transition is 29 kJ/mole of repeat unit. Fourier‐trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
50
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(52 citation statements)
references
References 9 publications
2
50
0
Order By: Relevance
“…For instance, when hexane is added to a solution of P-3BCMU in chloroform at room temperature, it turns blue [4] ; and when a solution of P-4BCMU in toluene is cooled from high temperature, it turns red [5]. These color transitions correspond to changes in the electronic structure of the carbon chain skeleton.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, when hexane is added to a solution of P-3BCMU in chloroform at room temperature, it turns blue [4] ; and when a solution of P-4BCMU in toluene is cooled from high temperature, it turns red [5]. These color transitions correspond to changes in the electronic structure of the carbon chain skeleton.…”
mentioning
confidence: 99%
“…On the other hand, it is generally believed that the conjugated backbone is in the trans configuration of the double bonds, but it has been suggested that yellow solutions consist primarily of the cis configuration [9]. Since [10], is related to pure intramolecular coil to rod conformational changes [5,[11][12][13] [14,15]. The second model corresponds to an aggregation of semi-rigid chains, or parts of such chains, leading to clusters [6,16] : this is the fringed micelles model [17].…”
mentioning
confidence: 99%
See 3 more Smart Citations